2014 16th International Conference on Transparent Optical Networks (ICTON) 2014
DOI: 10.1109/icton.2014.6876279
|View full text |Cite
|
Sign up to set email alerts
|

Low cost coherent receivers for UD-WDM NRZ systems in access networks

Abstract: This paper presents the first experimental achievements of the COCONUT project which aims at demonstrating ultra-dense Wavelength Division Multiplexing Passive Optical Networks (udWDM-PON) by means of low-cost coherent solutions. COCONUT should exploit low-cost optical components and simple electronics so that the cost of typical line terminals would be affordable to the end-users. Among different technical approaches considered within the project; we focus here on the solutions based on simple OOK-NRZ format.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…DSP to recover data from full coherent transmission is estimated to use 20W of the 32W available in CFP format transceivers [14]; this DSP-free receiver could therefore operate with at most 37.5% of the power consumption of a comparable fully coherent device. A simplified receiver [15] could be used to provide similar levels of performance, but either at the loss of polarisation diversity or a power budget penalty due to optical component losses, constraining the construction of the fibre network core.…”
Section: Switch Designmentioning
confidence: 99%
“…DSP to recover data from full coherent transmission is estimated to use 20W of the 32W available in CFP format transceivers [14]; this DSP-free receiver could therefore operate with at most 37.5% of the power consumption of a comparable fully coherent device. A simplified receiver [15] could be used to provide similar levels of performance, but either at the loss of polarisation diversity or a power budget penalty due to optical component losses, constraining the construction of the fibre network core.…”
Section: Switch Designmentioning
confidence: 99%
“…Coherent detection has been confirmed that it can improve the sensitivity and the spectrum efficiency in access network [12,13]. Compared with homodyne detection, heterodyne detection presents inherent image frequency interference, and as a result homodyne/intradyne reception is considered a better solution [14].…”
Section: Introductionmentioning
confidence: 98%